Impact of SARS-CoV-2 Genetic Blueprints on the Oral Manifestation of COVID-19: A Case Report - Khodavirdipour, Amir; Asadimanesh, Mahsa; Masoumi, Seyed Alireza (Global Medical Genetics, 2021)
Nonsegmented positive-sense RNA enveloped RNA severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus can result in coronavirus disease 2019 (COVID-19). This virus is from β-coronaviridae family of viruses. The common signs and symptoms of COVID-19 include pyrexia, cough, dyspnea, fatigue, myalgia, cephalgia, diarrhea, and nausea. Physicians and dentists around the world could directly link the COVID-19 and oral diseases such as ageusia and anosmia. After time passes, different aspects of symptoms of the diseases have been discovered. Research suggests that the oral cavity is the most vulnerable region for the virus because of angiotensin-converting enzyme-2 (ACE2) receptor abundance in the mouth. In this case report (no. of patients = 6), we would like to report significant findings in patients who were diagnosed with COVID-19 reported to our clinic during May 2021 complaining about the oral manifestation of it such as xerostomia, gingival inflammation, and cracked teeth. All patients are younger than 40 years with no history of dental complaints and oral diseases. Fortunately, these symptoms are not life threatening and treatable/manageable by current treatment options. To date, there is no clear proof of how and via which pathway, SARS-CoV-2 genomic blueprint causes the oral manifestation of COVID-19 beside ACE2 receptor which is the only known biopathway for such incidents.
Keywords: COVID-19; SARS-CoV-2; oral manifestation